Research On Entrepreneurial Intention Using Bibliometric Analysis - Resti Ramadhaniyati; Nani Sutarni; Kurjono Kurjono (UNIVED Press, 2024)
Using bibliometric analysis, the study examines entrepreneurial interests over the past five years. The data collected from the Scopus database was converted into 135 publications. Research shows that the publication is distributed in many of the most influential countries and cooperates with many other countries in this field. 1. Entrepreneurial interests; 2. Changes and cases; and 3. Cooperation between countries on entrepreneurship interests is the focus of this research. The results of the research can be used as a reference for other researchers who want to study this topic. It will help them understand the focus of research, establish a plan for advanced research, and be a comparison material and reference for other research to be done in the future.